SteE enhances the colonization of Salmonella Pullorum in chickens - Zhike Liu; Anatoliy Fotin; Roman Petrov; Jinyou Ma; Tetiana Fotina (Ukrainian Journal of Veterinary and Agricultural Sciences, 2023)
Salmonella pullorum (S. pullorum) is the causative agent of pullorum disease and results in severe economic losses in poultry, and can long-term survival by colonizing host organs. steE is an effector protein secreted by Salmonella pathogenicity island 2. It is not clear in vivo for the colonization of Salmonella. To investigate the role of steE on the colonization of S. Pullorum in the principal organs of chicken, we used S. pullorum and S. pullorum ΔsteE strains immunized chickens, respectively. The results of the virulence assay showed that the LD50 of S. pullorum ΔsteE was 22.8 times higher than that of S. pullorum in chickens. The colonization experiment of bacteria showed that the overall change trend of the number of S. pullorum and S. pullorum ΔsteE strains were similar in chicken liver, spleen, heart, bursa, and cecum, which increased first and then decreased. However, the deletion of steE caused significantly reduced colonization, pathological change, and virulence of S. pullorum in a chicken infection model. Our findings provide exciting insights into the pathogenic mechanism and live attenuated vaccine associated with steE in S. pullorum.